Genome Size Reversely Correlates With Host Plant Range in Helicoverpa Species - Zhang, Shen; Gu, Shaohua; Ni, Xinzhi; Li, Xianchun (Frontiers in Physiology, 2019)
In organisms with very low percentages of transposable elements (TEs), genome size may positively or negatively correlate with host range, depending on whether host adaptation or host modification is the main route to host generalism. To test if this holds true for insect herbivores with greater percentages of TEs, we conducted flow cytometry to measure the endopolyploidy levels and C-values of the host modification (salivary gland and mandibular gland in head), host adaptation (midgut), and host use-independent tissues (male gonad, hemolymph, and Malpighian tubules) of the generalist Helicoverpa armigera and the head of its specialist ancestor H. assulta. Larval salivary gland displayed a consecutive chain of endopolyploidy particles from 8Cx to higher than 32Cx and larval head and midgut had endopolyploidy nuclei clusters of 16Cx and 32Cx, whereas larval male gonad, hemolymph, and Malpighian tubules possessed no endopolyploidy nuclei of higher than 8Cx. The estimated genome size of the Solanaceae plant specialist H. assulta is 430 Mb, significantly larger than that of its generalist ancestor Heliothis virescens (408 Mb) and those of its two generalist descendants H. armigera (394 Mb) and H. zea (363 Mb). These data not only reveal a negative correlation between host plant range and genome size in this terminal lineage, but also imply that Helicoverpa species appear to depend more on host modification than on host adaptation to achieve polyphagy.